FAKTOR-FAKTOR YANG MEMPENGARUHI TURUNNYA HARGA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Faisal; Wage, Sunarto (LPPM Universitas Putera Batam, 2022)
The stock prices of automotive companies and their components experienced fluctuatingchanges but on average decreased, this decline was caused by an analysis of liquidity,activity and profitability. The purpose of this research is to see the effect of partial orsimultaneous liquidity, activity and profitability on the decline in stock prices of automotivecompanies and their components listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The type of data in this study is quantitative, the source of data in this study issecondary data with SPSS 22 analysis, the tests carried out are classical assumptiontests, multiple linear regression and also hypothesis testing with t-test and f-test. Thesample in this study is included in the type of purposive sampling. Partial results show thatliquidity has no effect on the decline in stock prices with a value (-1.449 < 2.007), activityaffects the decline in stock prices with a value (7.012 > 2.007), profitability does not affectthe decline in stock prices with a value (0.250 > 0.05) , Simultaneously liquidity, activityand profitability affect the decline in stock prices with (16,608 > 3.18). In conclusion,Liquidity has no effect on the decline in stock prices or H1 is rejected, Activity affects thedecline in stock prices or H2 is accepted, Profitability does not affect the decline in stockprices or H3 is rejected, Liquidity, Activity and Profitability affect the decline in stock pricesor H4 is accepted.